The Utility of Intravenous Acetaminophen in the Perioperative Period - O'Neal, Jason B. (Frontiers in Public Health, 2013)
Intravenous acetaminophen has rapid and effective analgesic properties. Recent studies have shown several benefits of using intravenous acetaminophen perioperatively. However, due to its relatively high cost and limited clinical data concerning its efficacy compared with other agents, physicians are hesitant to use intravenous acetaminophen in the perioperative period. This brief review examines the utility of this medication in the perioperative period and highlights future areas of clinical and epidemiological research regarding its use.